2007
DOI: 10.1152/ajprenal.00379.2006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro models of TGF-β-induced fibrosis suitable for high-throughput screening of antifibrotic agents

Abstract: Progressive fibrosis is a cause of progressive organ dysfunction. Lack of quantitative in vitro models of fibrosis accounts, at least partially, for the slow progress in developing effective antifibrotic drugs. Here, we report two complementary in vitro models of fibrosis suitable for high-throughput screening. We found that, in mesangial cells and renal fibroblasts grown in eight-well chamber slides, transforming growth factor-β1 (TGF-β1) disrupted the cell monolayer and induced cell migration into nodules in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 41 publications
3
82
0
1
Order By: Relevance
“…Results in this study indicated that emodin suppressed inflammation caused by CCl4, which might lead to the protection of the liver from injury. It is now widely accepted that the pro-inflammatory cytokine TGF-β1 is a major cytokine in the regulation of the production, degradation, and accumulation of ECM [38] , and it has been suggested that overexpression of TGF-β1 for a prolonged period of time after tissue damage may induce a fibroproliferative response and deposition of ECM, resulting in fibrosis in vital organs [39] . Many studies have detected the presence of TGF-β1, in the form of either protein or message, in the fibrotic tissues of animal models or human samples [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Results in this study indicated that emodin suppressed inflammation caused by CCl4, which might lead to the protection of the liver from injury. It is now widely accepted that the pro-inflammatory cytokine TGF-β1 is a major cytokine in the regulation of the production, degradation, and accumulation of ECM [38] , and it has been suggested that overexpression of TGF-β1 for a prolonged period of time after tissue damage may induce a fibroproliferative response and deposition of ECM, resulting in fibrosis in vital organs [39] . Many studies have detected the presence of TGF-β1, in the form of either protein or message, in the fibrotic tissues of animal models or human samples [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Picrosirius red staining allows the collagen produced by cell cultures to be quantified (Hu et al, 2009;Xu et al, 2007). Exposure of HK-2 cells to 50 and 5 mg/ml AS for 48 h did not modify the amount of collagen produced as compared to the control condition ( Figure 6).…”
Section: Cispt-induced Collagen Deposition Is Limited By As Co-treatmentmentioning
confidence: 97%
“…A second pool of four nontargeting siRNA oligos were used for negative-control experiments (Dharmacon nontargeting siGENOME SMART pool 2). C11 were transfected by electroporation according to the manufacturer's instructions as previously described (52).…”
mentioning
confidence: 99%